[PP.10.07] DEREGULATION OF SOLUBLE ADHESION MOLECULES IN RESISTANCE TO ANTIHYPERTENSIVE TREATMENT AND ITS ROLE IN CARDIOVASCULAR REMODELING. (September 2016) - De Faria, A.; Ritter, A.; Sabbatini, A.; Corrêa, N.; Brunelli, V.; Catharina, A.; Barbaro, N.; Almeida, A.; Modolo, R.; Moreno, H.
Abstract : Objective: Resistant hypertension (RHTN) and target organ damage are linked to increased inflammatory biomarkers, which may regulate adhesion molecules, such as (i) intracellular adhesion molecule-1 (ICAM-1), (ii) vascular adhesion molecule-1 (VCAM-1), (iii) the platelet (sP-selectin) and (iv) endothelial (sE-selectin) selectins. We aimed to investigate a previously unknown relationship between p-selectin, e-selectin, ICAM-1 and VCAM-1 with RHTN and target organ damage. Design and method: This cross-sectional study included 110 subjects diagnosed for true RHTN and 112 mild to moderate hypertensives (HTN). We determined blood pressure parameters, pulse wave velocity (PWV) and left ventricular mass index (LVMI). Adhesion molecules were determined by ELISA. The patients were grouped into those with LVMI > 95 g/m2 (females) and > 115 g/m2 (males) for comparisons of cardiac hypertrophy and PWV > 10m/s as having high arterial rigidity for comparisons of vascular damage. Results: Both sP-selectin and sE-selectin were increased; on the other hand sICAM-1 was reduced in RHTN compared with HTN patients, while similar levels of sVCAM-1 were encountered in the groups. sP-selectin e sVCAM-1 are elevated in the presence of arterial stiffness (sP-selectin: 104 ± 47 vs. 89 ± 45 ng/mL, p < 0.05; sVCAM-1: 1189 ± 411 vs. 1060 ± 412 ng/mL, p < 0.05) and cardiac hypertrophy (sP-selectin: 105 ± 51 vs. 88 ± 43 ng/mL, p < 0.05; sVCAM-1: 1170 ± 433 vs.1040 ± 383ng/mL, p < 0.05) in all hypertensives. sP-selectin predict both target organ damage after adjustment for age and BP levels. Apart from potential confounders, sE-selectin was considered independent predictor for RHTN. Conclusions: Our findings show the potential role of adhesion molecules, in particular sP-selectin on arterial stiffness and cardiac hypertrophy, and sE-selectin on resistance to antihypertensive therapy.